Influence of a phosphorus-based methacrylate monomer on features of thermally curable self-adhesive structural tapes. (October 2018) - Kowalczyk, Agnieszka; Kowalczyk, Krzysztof; Weisbrodt, Mateusz
Abstract: Thermally curable self-adhesive structural tapes (SATs) were prepared via UV-irradiation of a photoreactive epoxyacrylate copolymer compounded with a bisphenol-A type epoxy resin, a cationic hardener and modified with 2-hydroxyethyl methacrylate phosphate ester (G40). The influence of G40 addition on the self-adhesive features and thermal reactivity of the SATs as well as on the mechanical properties of thermally cured aluminum-SAT-aluminum overlap joints was analysed. The effect of various types of radical photoinitiators on the UV-photopolymerisation process of G40 was investigated as well. It was revealed that the addition of G40 increased adhesion of the SATs to aluminum, but it was also found that the UV-irradiation parameters (time and a UV dose applied during the SATs preparation process) were crucial for that feature. Moreover, G40 improved the shear strength of the thermally cured joints and significantly influenced epoxy groups conversion and crosslinking degree of the SATs.